Validation of diagnostic markers for streak virus disease resistance in maize - Sime, S.S.; Menkir, A.; Adetimirin, Victor O.; Gedil, Melaku A; Kumar, P. (MDPI, 2021)
Maize streak virus (MSV) is responsible for streak disease of maize and poses a serious threat to maize production in sub-Saharan Africa. Polygenic resistance to MSV has become an essential requirement in modern maize cultivars to mitigate yield losses. Many single nucleotide polymorphism (SNP) markers linked to putative MSV resistance loci have been identified for use in forward breeding. This study aimed to validate, using the high-throughput kompetitive allele specific PCR (KASP) assay, the diagnostic ability of the three SNP markers linked to the loci for the Msv1 resistance trait in 151 early generations inbred lines with diverse genetic backgrounds, together with nine MSV-resistant elite lines and a susceptible check (cv. Pool-16). The phenotypic responses were determined by MSV inoculation using viruliferous leafhoppers (Cicadulina triangular) under screenhouse conditions. Based on an established MSV disease rating system, the maize lines were categorized into resistant, moderately resistant, susceptible, and highly susceptible. The three SNPs associated with MSV resistance were detected in 133 lines, which were categorized as resistant (54), moderately resistant (76), and susceptible (1). The 18 early generation lines without these SNPs were classified as moderately resistant (10), susceptible (5), and highly susceptible (3). This study confirms the strong association of SNPs with MSV resistance and their usefulness for forward breeding in maize while emphasizing the need to identify additional markers to screen lines for MSV resistance without any ambiguity.